Pedestrian facilities : engineering and geometric design - Schoon, John G. 1937- (Thomas Telford, 2010)
Deals with the engineering and numerical design aspects of pedestrian facilities, such as footways, uncontrolled and controlled crossings along roads and at junctions, roundabouts and driveways where pedestrian and vehicular traffic interact. This title focuses on the dimensional aspects of pedestrian facilities.
Keywords: Pedestrian facilities design.; Pedestrian areas.; Civil engineering.; elektronické knihy; electronic books